2011
DOI: 10.1111/j.1365-2842.2011.02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing abbreviated OHIP versions for use with TMD patients

Abstract: The aim of this study was to evaluate the psychometric characteristics of three versions of the Dutch Oral Health Impact Profile (OHIP-NL), for clinical use with temporomandibular disorder (TMD) patients. To that end, two abbreviated OHIP versions (OHIP-NL14 and OHIP-NL5) were developed by respectively selecting 14 and five items from the officially translated and culturally adapted original 49-item OHIP-NL questionnaire. A total of 245 consecutive patients, referred by their dentist to the TMD clinic of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 30 publications
(64 reference statements)
3
52
0
Order By: Relevance
“…The results of this study are in line with previous results using the OHIP-49 with TMD patients 6,12 , but it is more difficult to compare directly to previous studies examining ADP with the OHIP because of the variety of methods used 13,14,28,29 . Even though, the actual OHIP-14 was not used, instead the appropriate 14 items were extracted out of the OHIP-49 questionnaire; our results are comparable to other studies that have used the OHIP-14 with TMD and ADP patients [28][29][30] . It would, however, appear that given the near perfect correlations between the OHIP-49, the OHIP-14, and the OHIP-5 that short versions of the OHIP measure pain's impact on OHRQoL very well.…”
Section: Discussionsupporting
confidence: 81%
“…The results of this study are in line with previous results using the OHIP-49 with TMD patients 6,12 , but it is more difficult to compare directly to previous studies examining ADP with the OHIP because of the variety of methods used 13,14,28,29 . Even though, the actual OHIP-14 was not used, instead the appropriate 14 items were extracted out of the OHIP-49 questionnaire; our results are comparable to other studies that have used the OHIP-14 with TMD and ADP patients [28][29][30] . It would, however, appear that given the near perfect correlations between the OHIP-49, the OHIP-14, and the OHIP-5 that short versions of the OHIP measure pain's impact on OHRQoL very well.…”
Section: Discussionsupporting
confidence: 81%
“…This is in line with the findings of the current study, as high internal consistency was found for the respective 15 items. An OHIP-5 questionnaire with only 5 items was introduced by van der Meulen [24]. The OHIP-5 is as concise as the WHO-5 and can therefore be answered in a short time.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations >0.50 are indicative of concurrent validity. In addition, the OHIP-14 and the OHIP-5 were extracted from the OHIP-49 questionnaire, as these instruments use only some of the items of the OHIP-49 [23,24]. For both instruments, Cronbach's α was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some reduced versions, such as the OHIP-14 (Slade, 1997), were developed to address the same concepts as the full version of OHIP but to consume less time. These versions have been adapted and validated for specific clinical conditions, such as temporomandibular disorders (Van der Meulen et al, 2012), prostheses users (Özhayat and Gotfredsen, 2013), and edentulous patients (de Souza et al, 2012), among others.…”
mentioning
confidence: 99%